Freedom and growth : the rise of states and markets in Europe, 1300-1750 - Epstein, Stephan R., 1960-2007 (Routledge explorations in economic history., 2000)
This book examines whether different kinds of 'freedoms' (absolutist, parliamentary and republican) caused different economic outcomes, and shows the effect of different political regimes on long term development.